Causes of the 1997 Asian Financial Crisis: What Can an Early Warning System Model Tell Us? - Juzhong Zhuang; J. Malcolm Dowling (Asian Development Bank (ADB), 2002)
"Using an early warning system (EWS) model, this paper provides more empirical evidence on the causes of the 1997 Asian financial crisis, with a view to discriminating between the two hypotheses of "weak fundamentals" and "investors' panic." The results show that there are strong warning signals of heightened financial vulnerability in each of the five most affected countries from the EWS model prior to the crisis, suggesting that weaknesses in economic and financial fundamentals in these countries played an important role in triggering the crisis. The warning signals point to fundamental weaknesses including real appreciations of domestic currencies, deteriorations in current account positions, excessive external borrowings by banks and currency mismatches in their balance sheets, excessive growth of domestic credit, economic slowdown, and the burst of asset price bubbles."
hdl:11540/2065
Keywords: 330; Währungskrise; Frühwarnsystem; Prognose; Asien; Finanzkrise